2015
DOI: 10.3389/fphys.2015.00218
|View full text |Cite
|
Sign up to set email alerts
|

Direct conscious telemetry recordings demonstrate increased renal sympathetic nerve activity in rats with chronic kidney disease

Abstract: Chronic kidney disease (CKD) is associated with sympathetic hyperactivity and impaired blood pressure control reflex responses, yet direct evidence demonstrating these features of autonomic dysfunction in conscious animals is still lacking. Here we measured renal sympathetic nerve activity (RSNA) and mean arterial pressure (MAP) using telemetry-based recordings in a rat model of CKD, the Lewis Polycystic Kidney (LPK) rat, and assessed responses to chemoreflex activation and acute stress. Male LPK and Lewis con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
1
7
0
7
Order By: Relevance
“…Another consideration is that our sympathetic nerve recording data analysis is reported as absolute value microvolt recordings from multifiber sympathetic nerve preparations. While differences in the contact between the nerve and electrode can result in differences in the microvolt signal amplitude, our work, in this study and previously under both conscious (Salman et al, 2015a) and anesthetized conditions (Yao et al, 2015;Saha et al, 2019), demonstrated SNA at baseline was heightened in the LPK model with a low level of variance within each group of animals. This is consistent with the work of others who similarly report SNA data when comparing baseline activity between different groups of animals (Guild et al, 2010;Stocker and Muntzel, 2013;Burke et al, 2016;Ong et al, 2019) and, importantly, as presented in the seminal study in this field by Simms et al (2009), who used microvolt data to measure respiratory and sympathetic responses to changes in chemoreceptor stimuli in the SHR rat.…”
Section: Study Limitationssupporting
confidence: 45%
“…Another consideration is that our sympathetic nerve recording data analysis is reported as absolute value microvolt recordings from multifiber sympathetic nerve preparations. While differences in the contact between the nerve and electrode can result in differences in the microvolt signal amplitude, our work, in this study and previously under both conscious (Salman et al, 2015a) and anesthetized conditions (Yao et al, 2015;Saha et al, 2019), demonstrated SNA at baseline was heightened in the LPK model with a low level of variance within each group of animals. This is consistent with the work of others who similarly report SNA data when comparing baseline activity between different groups of animals (Guild et al, 2010;Stocker and Muntzel, 2013;Burke et al, 2016;Ong et al, 2019) and, importantly, as presented in the seminal study in this field by Simms et al (2009), who used microvolt data to measure respiratory and sympathetic responses to changes in chemoreceptor stimuli in the SHR rat.…”
Section: Study Limitationssupporting
confidence: 45%
“…Compared with normotensive counterparts, elevations in basal RSNA are present in the SHR (demonstrated by direct nerve recording) 39 , and in patients with essential hypertension (demonstrated by increased renal norepinephrine spillover) 40 . There is also evidence for elevated RSNA in chronic kidney disease 41 44 . Although we have not directly measured RSNA in the sheep with hypertensive CKD, we have demonstrated hyperinnervation of renal efferent sympathetic and renal afferent sensory nerves together with enhanced vascular contraction to renal nerve stimulation 28 , 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the species found to be decreased in CKD are among those that strengthen gut barrier function [16,36,37]; produce anti-inflammatory [46,71,73,109], NO [16,47], CDCA, UDCA [50,[83][84][85], GABA [60,61,110], Ach [65,107,108], and the vitamin B complex [17, 52-54, 81, 82]; increase the production of gut hormones with anti-inflammatory properties [57][58][59][76][77][78][79]; increase anti-inflammatory vagal activity [90,93,97]; and decrease pro-inflammatory renal sympathetic activity. Interestingly, CKD is associated with gut barrier dysfunction, an increase in uremic toxins [101], elevated renal sympathetic activity [111], lower group B vitamin levels [112][113][114] and NO [115], and a reduction in vagal activity [116], which may stem from the gut dysbiosis found in patients with CKD. Therefore, we can suggest that a healthy gut microbiota can protect from CKD, whereas gut dysbiosis takes part in the development and progression of CKD through a number of pathways that manipulate host inflammatory activity.…”
Section: Gut-kidney Crosstalk and Inflammation In The Development Of Ckdmentioning
confidence: 99%